Knowledge automation : how to implement decision management in business processes - Fish, Alan N. (Hoboken, N.J. : John Wiley & Sons, 2012)
'A proven decision management methodology for increased profits and lowered risksAutomating Decisions in Business Processes describes a simple but comprehensive methodology for decision management projects, which use business rules and predictive analytics to optimize and automate small, high-volume business decisions. It includes Decision Requirements Analysis (DRA), a new method for taking the crucial first step in any IT project to implement decision management: defining a set of business decisions and identifying all the information--business knowledge and data--required to make those decisions. Describes all the stages in automating business processes, from business process modeling down to the implementation of decision services Addresses how to use business rules and predictive analytics to optimize and automate small, high-volume business decisions Proposes a simple'top-down' method for defining decision requirements and representing them in a single diagram Shows how clear requirements can allow decision management projects to be run with reduced risk and increased profit Nontechnical and accessible, Automating Decisions in Business Processes reveals how DRA is destined to become a standard technique in the business analysis and project management toolbox'--
Includes index.
Includes bibliographical references (p. 162-169) and index.
Keywords: Information technology; Decision making